2000
DOI: 10.1002/1521-3765(20001002)6:19<3491::aid-chem3491>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Classification of Lewis Acids on the Basis of Activity and Selectivity

Abstract: Group 3-15 metal chlorides (Lewis acids) were classified on the basis of activity and aldehyde- and aldimine-selectivity in an addition reaction of a silyl enol ether. Based on the experimental results, metal chlorides (Lewis acids) were classified as follows: A, active; B, weak; C, inactive for the activation of the aldehyde and/or aldimines. Groups A and B were further divided into A-1 or B-1 (aldehyde-selective), A-2 or B-2 (aldimine-selective), and A-3 or B-3 (neutral). The final classification is as follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(68 citation statements)
references
References 25 publications
4
63
1
Order By: Relevance
“…NbCl 5 forms chloro-bridged dimers in its solid state in which each niobium atom is surrounded by a distorted octahedron of chlorine atoms. NbCl 5 is highly electrophilic and can act as a Lewis acid, promoting several organic transformations (Batista et al, 1997;Kobayashi et al, 2000;Constantino et al, 2001Constantino et al, , 2004Constantino et al, , 2005Constantino et al, , 2007Andrade, 2004;da Silva-Filho et al, 2005Andrade & Rocha, 2006;Wang et al, 2007;Polo et al, 2008;Cai et al, 2010;Hou et al, 2010Hou et al, , 2011Lacerda et al, 2012;Liu et al, 2013;Martins et al, 2013;dos Santos et al, 2013;Bian et al, 2014;Nasseri et al, 2014).…”
Section: Introductionsupporting
confidence: 81%
“…NbCl 5 forms chloro-bridged dimers in its solid state in which each niobium atom is surrounded by a distorted octahedron of chlorine atoms. NbCl 5 is highly electrophilic and can act as a Lewis acid, promoting several organic transformations (Batista et al, 1997;Kobayashi et al, 2000;Constantino et al, 2001Constantino et al, , 2004Constantino et al, , 2005Constantino et al, , 2007Andrade, 2004;da Silva-Filho et al, 2005Andrade & Rocha, 2006;Wang et al, 2007;Polo et al, 2008;Cai et al, 2010;Hou et al, 2010Hou et al, , 2011Lacerda et al, 2012;Liu et al, 2013;Martins et al, 2013;dos Santos et al, 2013;Bian et al, 2014;Nasseri et al, 2014).…”
Section: Introductionsupporting
confidence: 81%
“…It has been reported that the Strecker reaction of acetophenone even with the activated amine 3,4,5-trimethylaniline using metal triflates and acetonitrile as the solvent gave very poor yield of the product (47)(48)(49). We found that a similar reaction of acetophenone with aniline and TMSCN (cyanide source) in dichloromethane using Ga(OTf) 3 as a catalyst proceeds smoothly under mild conditions (room temperature, 5 h) giving the corresponding ␣-aminonitrile in excellent yield and high purity ( Table 2, entry 1), despite that the direct Strecker reaction using aromatic ketones and aromatic amines has been repeatedly cited in the literature as a challenge (6,7,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Resultsmentioning
confidence: 77%
“…The Strecker reaction with aldehydes has been studied extensively with a variety of catalysts (37-46) including a number of metal triflates (47)(48)(49). However, the reactions are not feasible for ketones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction mechanism is considered to involve a ternary complex, in which both the 1,3-dicarbonyl compound and the enone are coordinated to a Lewis-acid metal center. 58 A shift in the infrared (IR) spectrum of the coordinated ketone is a measure of the Lewis-acid strength of metal cations. 95 The IR spectrum of the (CO) band of adsorbed cyclopentanone onto Cu 2þ -mont appeared at 1685 cm À1 , which nþ -monts play an important role in these carbon-carbon bond-forming reactions.…”
mentioning
confidence: 99%